Paroxysmal Nocturnal Hemoglobinuria Superimposed with Preeclampsia - Mann-Ling Chen; Chen-Hsiang Yu; Fong-Ming Chang; Pao-Lin Kuo (Elsevier, 2006)
Objective: Paroxysmal nocturnal hemoglobinuria (PNH) is a rare hematologic disorder characterized by complement-mediated intravascular hemolysis. As maternal complication of PNH is already severe, it becomes much more complex when preeclampsia is superimposed. We present a case of PNH superimposed with severe preeclampsia in the third trimester. Case Report: A 30-year-old, gravida 1, para 0, woman had PNH, diagnosed at the age of 17. Her PNH was stable under medication. In 2004, she conceived and had prenatal care at our hospital. At 35 weeks of gestation, preeclampsia with elevated blood pressure and proteinuria were superimposed and managed with close surveillance. A live male baby was delivered vaginally at 38 weeks of gestation. During parturition, her blood pressure increased to 180/100 mmHg. Thrombocytopenia, hyponatremia, hyperkalemia, hypoalbuminemia, elevated liver enzymes and lactate dehydrogenase were also noted. Preeclampsia continued to postpartum and eventually disappeared. Conclusion: The most frequent causes of PNH-related fetomaternal morbidity and mortality are hemolysis and thrombosis. The situation becomes even more complicated when PNH is superimposed with preeclampsia. Appropriate clinical surveillance, awareness of the potential risks of hemolysis and thrombosis, as well as evaluation of fetal wellbeing are essential.